Serum Vitamin D Levels and Pelvic Bone Mineral Density in Postmenopausal Women: A Biochemical Study - Umaira Maqsood, Farah Saleem, Salman Habib Abbasi, Abdur Rauf Hammad, Muhammad Azhar Khan, Muhammad Yousuf Memon, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Vitamin D is essential for calcium absorption and bone mineralization, particularly in postmenopausal women who are at high risk of osteoporosis due to estrogen deficiency. Low vitamin D levels impair skeletal metabolism and contribute to bone loss, increasing the risk of pelvic and hip fractures. Objective: To assess the association between serum vitamin D levels and pelvic bone mineral density (BMD) among postmenopausal women attending gynaecology clinics at Dr. Faisal Masood Teaching Hospital, Sargodha, and Al-Nafees Medical College and Hospital, Islamabad. Methods: This cross-sectional biochemical study was conducted from June 2022 to March 2023 on 150 postmenopausal women aged 45–70 years. After ethical approval and informed consent, participants were evaluated through clinical examination and laboratory testing. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured using the ELISA method, while pelvic BMD was assessed by Dual-Energy X-Ray Absorptiometry (DEXA). Participants were categorized as vitamin D deficient (<20 ng/mL), insufficient (20–30 ng/mL), or sufficient (>30 ng/mL). Statistical analysis was performed using SPSS version 26, applying Pearson’s correlation and multiple linear regression to explore associations between vitamin D and BMD. Results: The mean age of participants was 57.9 ± 6.2 years, with a mean menopausal duration of 8.3 ± 3.1 years. Vitamin D deficiency was observed in 63.3% of women, insufficiency in 24.7%, and sufficiency in 12.0%. The mean serum vitamin D level was 19.1 ± 7.3 ng/mL, and the mean pelvic BMD was 0.77 ± 0.13 g/cm². A significant positive correlation was found between serum vitamin D levels and pelvic BMD (r = 0.52, p < 0.001). Regression analysis revealed that vitamin D was an independent predictor of BMD (β = 0.38, p = 0.002) after adjusting for age, BMI, and menopausal duration. Conclusion: Serum vitamin D levels showed a strong positive association with pelvic bone mineral density in postmenopausal women. Vitamin D deficiency is highly prevalent and significantly contributes to bone loss, emphasizing the importance of routine screening and supplementation to prevent osteopenia and osteoporosis in this vulnerable group. Keywords: Vitamin D, Bone Mineral Density, Postmenopausal Women, Pelvic Bone, Osteoporosis, Biochemical Study